ANALISIS PENERAPAN SOP DAN TATA LETAK TOKO DALAM MENINGKATKAN EFEKTIVITAS OPERASIONAL (STUDI KASUS PADA GALERY KEBAYA TANAH ABANG) - Hikmal Firdaus; Djoko Hananto (Taksasila Edukasi Insani, 2026)
The shift in consumer purchasing behavior toward digital platforms has created significant challenges for traditional retail SMEs, including fashion businesses in Tanah Abang Market, making operational effectiveness an increasingly urgent issue. Galery Kebaya Tanah Abang has experienced a decline in operational performance despite the growing national trend of kebaya fashion, indicating internal problems related to work systems. This study aims to analyze the implementation of Standard Operating Procedures (SOP) and store layout and examine how both contribute to improving operational effectiveness. The research questions focus on how SOP and store layout are implemented and how they affect the operational effectiveness of Galery Kebaya. This study adopts a qualitative descriptive approach with an intrinsic case study design. Data were collected through in-depth interviews with the owner and employees, field observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that SOP implementation is inconsistent and the store layout is inefficient, resulting in irregular workflows, weak inventory control, and slow customer service. These findings demonstrate that SOP and store layout are interrelated and must be integrated to enhance the operational effectiveness of traditional fashion SMEs. The study concludes that strengthening SOP implementation and redesigning the store layout in a contextual manner are essential strategies for conventional market SMEs to adapt to changes in the business environmentKeywords : Management Operations, Operational Effectiveness, SMEs, Standard Operating Procedures, Store Layout.